Correlates of Silence: Enhanced Microstructural Changes in the Uncinate Fasciculus - Ben-Soussan, Tal Dotan; Marson, Fabio; Piervincenzi, Claudia; Glicksohn, Joseph; De Fano, Antonio; Amenduni, Francesca; Quattrocchi, Carlo C.; Carducci, Filippo (Frontiers in Psychology, 2020)
Silence is an important aspect of various meditation practices, but little work has focused specifically on the underlying neurophysiology of silence-related meditative practice, and on how it relates to the self-reported experiences of practitioners. To expand current knowledge regarding the neurophenomenology of silence in meditation, we directly investigated first-person reports of silence-related experiences during the practice of Quadrato Motor Training (QMT) and their association with changes in fractional anisotropy (FA). Participants recorded their cognitive, emotional, and physical experiences upon beginning QMT and again after 6 weeks of QMT practice. These reports were evaluated qualitatively and quantitatively. Findings showed that change between the two time points in self-reported silence-related experiences was negatively correlated with change in attentional effort, and positively correlated with changes in the left uncinate fasciculus. These results expand current knowledge regarding the neuroanatomical correlates of silence-related experiences during meditation.